The powers of distance : cosmopolitanism and the cultivation of detachment / Amanda Anderson. - Anderson, Amanda (Princeton University Press, 2001)
Combining analysis of Victorian literature and culture with forceful theoretical argument, this text examines the progressive potential of those forms of cultivated detachment associated with Enlightenment and modern thought.